Budgetary Adjustments to Deal with the Postponement of the New VAT Law : Bangladesh Policy Note - World Bank (World Bank, Washington, DC, 2018)
Postponement of 2012 VAT Law requires significant early adjustments in the FY18 Budget to tap additional sources of revenue and expenditure saving to increase fiscal space. Automation, process simplification, and dispute resolution may bring additional tax revenues in the immediate future. These are elaborated in an earlier note dated July 22, 2017. This note focusses on developments in non-development capital expenditures, loans and advances, and block allocations in the revenue budget that can generate significant expenditure saving in addition to the usual ADP implementation shortfall. These can be complemented by reforms that will help enhance concessional external financing to ease the pressure on the relatively more expensive domestic financing of the budget deficit.